Hard X-ray one dimensional nano-focusing at the SSRF using a WSi2/Si multilayer Laue lens - 黄秋实 李浩川 宋竹青 朱京涛 王占山 李爱国 闫帅 毛成文 王华 闫芬 张玲 余笑赛 刘鹏 李明 (中国物理C：英文版, 2013)
The multilayer Laue lens （MLL） is a novel diffraction optics which can realize nanometer focusing of hard X-rays with high efficiency. In this paper, a 7.9 μm-thick MLL with the outmost layer thickness of 15 nm is designed based on dynamical diffraction theory. The MLL is fabricated by first depositing the depth-graded multilayer using direct current （DC） magnetron sputtering technology. Then, the multilayer sample is sliced, and both cross-sections are thinned and polished to a depth of 35–41 μm. The focusing property of the MLL is measured at the Shanghai Synchrotron Facility （SSRF）. One-dimensional （1D） focusing resolutions of 205 nm and 221 nm are obtained at E=14 keV and 18 keV, respectively. It demonstrates that the fabricated MLL can focus hard X-rays into nanometer scale.